Analysis of the Implementation of Article 22 of Law Number 23 of 2011 Concerning Management of Zakat as a Reduction of Taxable Income in the City of Palu From Maqāṣhid Al-Syarīʿah Perspective - Sari Sakinah; Zainal Abidin; Gani Jumaat; Fatimawali, Fatimawali; Ermawati, Ermawati (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2024)
Zakat is the third pillar of Islam, so most Muslims know the importance of paying Zakat. Indonesia has related regulations, namely Law of the Republic of Indonesia No. 23 of 2011 concerning the management of Zakat; Article 22 states, "Zakat paid by muzak to the National Amil Zakat Agency or Amil Zakat Institution is deducted from taxable income. The type of research in this research is field research. The primary and secondary data are used. Data collection techniques are observation, interviews, and documentation. The results of this research show that the mechanism for implementing this law is contained in Minister of Finance Regulation Number 254/PMK.03/2010 concerning Procedures for Charging Zakat or Mandatory Religious Contributions That Can Be Deducted from Gross Income, namely Zakat on income paid by the Compulsory Taxation of individuals who adhere to the Islamic religion or by taxpayers of domestic corporate bodies owned by followers of the Islamic religion to National Zakat Amil Agency or zakat amil institutions established or authorized by the Government, by attaching Proof of Zakat Deposit at the time of reporting the annual Tax Return no later than March 31 of the current year, representing the intention of Maqāṣhid Al-Syarīʿah itself in achieving the goal of benefit both in the world and the benefit in the afterlife, Law Number 23 of 2011 concerning zakat management regulates Zakat as a deduction from taxable income, with the aim of exempting taxpayers Muslims have two responsibilities, namely paying taxes and Zakat. Research implications: It is necessary to carry out outreach efforts regarding Zakat as a deduction from taxable income. Taxpayers and entrepreneurs who are subject to tax are expected to pay Zakat through official government institutions that handle Zakat, such as the National Zakat Amil Agency and the Zakat Amil Institute.